COL17A1 editing via homology-directed repair in junctional epidermolysis bullosa - Petković, Igor; Bischof, Johannes; Kocher, Thomas; March, Oliver Patrick; Liemberger, Bernadette; Hainzl, Stefan; Strunk, Dirk; Raninger, Anna Maria; Binder, Heide-Marie; Reichelt, Julia; Guttmann-Gruber, Christina; Wally, Verena; et al. (Frontiers in Medicine, 2022)
Background: Epidermolysis bullosa (EB), a severe genetic disorder characterized by blister formation in skin, is caused by mutations in genes encoding dermal-epidermal junction proteins that function to hold the skin layers together. CRISPR/Cas9-induced homology-directed repair (HDR) represents a promising tool for editing causal mutations in COL17A1 in the treatment of junctional epidermolysis bullosa (JEB). Methods: In this study, we treated primary type XVII collagen (C17)-deficient JEB keratinocytes either with Cas9 nuclease or nickase (Cas9n) ribonucleoproteins (RNP) and a single-stranded oligonucleotide (ssODN) HDR template in order to correct a causal pathogenic frameshift mutation within the COL17A1 gene. Results: As analyzed by next generation sequencing of RNP-nucleofected keratinocytes, we observed an HDR efficiency of ~38% when cells were treated with the high-fidelity Cas9 nuclease, a mutation-specific sgRNA, and an ssODN template. The combined induction of end joining- and HDR-based repair pathways resulted in a C17 restoration efficiency of up to 60% as assessed by flow cytometry. Furthermore, corrected JEB keratinocytes showed a significantly increased adhesive strength to laminin-332 and an accurate deposition of C17 along the basement membrane zone (BMZ) upon differentiation into skin equivalents. Conclusion: Here we present a gene editing approach capable of reducing end joining-generated repair products, while increasing the level of seamless HDR-mediated gene repair outcomes, thereby providing a promising CRISPR/Cas9-based gene editing approach for JEB.